Economic Assessment of the Efficiency of Organic Crop Production in the South Ural's Regions in Russia - Nikolai D. ZAVODCHIKOV; Tatiana N. LARINA; Dmitriy A. SIUSIURA (Communications of International Proceedings, 2020)
The production of organic crop products is a profitable direction for the development of agriculture in Russia. Most of the agricultural land in Russia is not contaminated with chemicals. Many vast territories are located in ecologically clean areas. Reasons that hinder the development of organic agriculture are the following: lack of targeted governmental financial support, farmers’ lack of awareness about the difference between certified organic products and non-certified products et cetera. The authors of the article analyzed data from the National Organic Union of Russia, FiBL, IFOAM on the level of development of organic production in Russia and other countries. A more detailed analysis was carried out according to the Rosstat data in the context of the regions of the South Ural. Taking the present conditions of the Orenburg region and utilizing an optimization model, the authors substantiated the structure of production costs and assessed the economic efficiency of the production of winter and spring wheat with the usage of the traditional technology and of the methods associated with organic technology.
Keywords: Organic Products; Crop Production; Assessment; Economic Efficiency.